The impact of social determinants of health on infant and maternal health using a reproductive justice lens - Kathryn J. Malin; Ashelee J. Vance; Stephanie E. Moser; Jessica Zemlak; Cherise Edwards; Rosemary White-Traut; Rebecca Koerner; Jacqueline McGrath; Kelly McGlothen-Bell (BMC Pregnancy and Childbirth)
Abstract Background Rates of preterm birth, low birth weight, and Neonatal Intensive Care Unit (NICU) admissions continue to rise in the United States (US). Social determinants of health (SDOH) are recognized as significant contributors to infant and maternal health, underscoring the need for use of research frameworks that incorporate SDOH concepts. The Restoring Our Own Through Transformation (ROOTT) theoretical framework is rooted in reproductive justice (i.e. reproductive rights and social justice-based framework) and emphasizes both structural and social determinants as root causes of health inequities. The impact of SDOH on maternal and infant mortality and morbidity can often be traced to structural determinants unique to the US, including slavery, Jim Crow laws, redlining, and the GI Bill. Aims Using data from the Pregnancy Risk Assessment Monitoring System (PRAMS) 8 database, we aimed to evaluate relationships between SDOH (as guided by the ROOTT Framework) and maternal and infant health outcomes. Methods Data were analyzed from 11 states that included the SDOH supplement in their PRAMS 8 data collection. We used bivariate analyses to examine relationships between SDOH measures guided by the ROOTT framework (e.g. abuse during pregnancy, access to prenatal care, housing stability and education) and maternal morbidity (i.e., gestational hypertension and gestational diabetes) and infant outcomes (i.e., preterm birth, NICU admission, breastfeeding). Pre-identified covariates were controlled for in the logistic and linear regression models. Results Preterm birth, NICU admission, breastfeeding, and maternal morbidities were significantly associated with SDOH measures linked to structural determinants in the US. Abuse during pregnancy, access to prenatal care, housing, and education were all significantly associated with poorer infant health outcomes in the final regression models. Women who received prenatal care beginning in the 3rd trimester were twice as likely to develop gestational hypertension. Conclusions SDOHs rooted in structural determinants are important predictors of poorer maternal and infant health outcomes. Evaluating health outcomes using a reproductive justice framework reveals modifiable risk factors, including access to stable healthcare, safety, and housing. Comprehensive healthcare provision must ensure early and consistent access to healthcare and resources for safety and housing stability to support maternal and infant health.